Pregabalin and Its Involvement in Coronial Cases. Issue 1 (16th May 2019) - Thompson, Amanda; Morey, Sarah; Griffiths, Andrew
Abstract: Pregabalin is an anticonvulsant and analgesic designed to treat neuropathic pain and partial seizure disorders and has been available in Australia as a prescription medication since 2005. Studies have found high rates of polydrug use associated with pregabalin and it is reportedly used recreationally for its euphoric and relaxing effects as well as to self-manage opioid withdrawal symptoms. A robust analytical method for the analysis of pregabalin using protein precipitation and LC/MS/MS was developed, validated and employed in routine case work. In recent years a substantial increase in pregabalin detections in coronial case submissions had been noted. This study examines the case characteristics and outcomes of 332 coronial cases submitted to the laboratory and analyzed for pregabalin between 2015 and 2017. Pregabalin was identified in approximately 5% of all coronial cases submitted during this time. A high rate of concurrent drug use with pregabalin was evident with the predominant classes being opioids, benzodiazepines and anti-depressants. Post-mortem blood pregabalin concentrations ranged from <0.05 to 140 mg/kg (median 5.5 mg/kg); however, limited interpretation of levels could be achieved as the drug was rarely identified in the absence of other drugs. Cause of death (COD) was found to be drug related in 58% of all cases, with mixed drug toxicity specifically mentioned as related to COD in 40% of cases.